177 Strategies to improve the efficiency of beef cattle production. (5th December 2019) - McAllister, Tim A; Basarab, John; Guan, Leluo
Abstract: Globally there are approximately 1 billion beef cattle raised in both intensive and extensive production systems and of the principal livestock species, beef cattle are known to have the poorest feed efficiency. As a result of low feed efficiency, cattle also have a larger environmental footprint per kg of product produced. However, these metrics fail to consider that beef cattle produce high quality protein from feeds that are largely unsuitable for other livestock species. Even in Canada's intensive beef production system, forages account for more than 80% of feed, with high grain diets only being fed for 3 to 4 months during finishing. Strategies to improve the efficiency of beef cattle are focusing on the genetics of the host, the functional efficiency of the gastrointestinal microbiome and the structure and composition of the feed. Maintenance of hybrid vigor is central to matching the optimal biological type of animal to a variety of management practices and environments. Genotyping can play a key role in ensuring hybrid vigor is maintained so that populations can adapt to changing environmental conditions brought about by influences such as climate change. The central role of microbiome-host interactions in the efficient digestion and absorption of nutrients from the digestive tract is becoming increasingly apparent. Microbial markers and gene expression patterns within the intestinal microbiome are being used to identify efficient hosts and to alter the microbiome in a manner that enhances fibre digestion. Finally, feed types and feed processing are being optimized to maximize the value that can be derived from both forages and concentrates. This multi-faceted approach to improving efficiency is coupled with strategies that reduce disease and improve host health. Strategies to improve the efficiency of cattle production are a perquisite for the sustainable intensification that is needed to satisfy the future demand for beef.